Detection of Mesospheric CO2 Ice Clouds on Mars in Southern Summer. Issue 14 (19th July 2019) - Jiang, F. Y.; Yelle, Roger V.; Jain, S. K.; Cui, J.; Montmessin, F.; Schneider, N. M.; Deighan, J.; Gröller, H.; Verdier, L.
Abstract: This paper reports the first detections of two high‐altitude nighttime CO2 clouds on Mars during southern summer ( L s =264° and L s =330°) with stellar occultation measurements by the Imaging Ultraviolet Spectrograph on board the Mars Atmosphere and Volatile Evolution spacecraft. Interpretation of the transmission spectra with Mie theory indicates particle radii of ∼90–110 nm assuming a monodisperse distribution. The altitude profile of extinction indicates that the cloud layers are confined horizontally to sizes less than ∼500–700 km. Examination of the CO2 density and temperature profiles reveals strong wave‐like perturbations. Supersaturated temperatures occur at the maximum negative extent of these wave‐like perturbations, which are organized in longitude with a dominant m =3 zonal harmonic. This suggests that tides are important in the formation of CO2 clouds. Key Points: We report the first detections of two high‐altitude nighttime CO2 clouds on Mars during southern summer The altitude profile of extinction indicates that the cloud layers are confined horizontally to sizes less than ∼500–700 km Examination of the CO2 density and temperature profiles reveals that tides are important in the formation of Martian CO2 clouds